2019
DOI: 10.1017/s0954579419000580
|View full text |Cite|
|
Sign up to set email alerts
|

Pubertal development mediates the association between family environment and brain structure and function in childhood

Abstract: Psychosocial acceleration theory suggests that pubertal maturation is accelerated in response to adversity. In addition, suboptimal caregiving accelerates development of the amygdala–medial prefrontal cortex circuit. These findings may be related. Here, we assess whether associations between family environment and measures of the amygdala–medial prefrontal cortex circuit are mediated by pubertal development in more than 2000 9- and 10-year-old children from the Adolescent Brain Cognitive Development Study (htt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(140 citation statements)
references
References 136 publications
(191 reference statements)
11
125
4
Order By: Relevance
“…Thus, adolescents in this sample who had experienced more negative life events may have adapted to more stressful contexts via accelerated maturation in CO-amygdala-hippocampal connections. Consistent with this finding, a recent investigation with ABCD data found that accelerated pubertal maturation mediated the association between stressful family environments and CO network-amygdala rsFC ( Thijssen et al, 2020a , Thijssen et al, 2020b ). The current longitudinal findings also extend prior cross-sectional evidence of stress acceleration in cortico-limbic circuitry ( Gee et al, 2013a , Herzberg et al, 2021 , Miller et al, 2020 , Silvers et al, 2016 , Thijssen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Thus, adolescents in this sample who had experienced more negative life events may have adapted to more stressful contexts via accelerated maturation in CO-amygdala-hippocampal connections. Consistent with this finding, a recent investigation with ABCD data found that accelerated pubertal maturation mediated the association between stressful family environments and CO network-amygdala rsFC ( Thijssen et al, 2020a , Thijssen et al, 2020b ). The current longitudinal findings also extend prior cross-sectional evidence of stress acceleration in cortico-limbic circuitry ( Gee et al, 2013a , Herzberg et al, 2021 , Miller et al, 2020 , Silvers et al, 2016 , Thijssen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
“…Theoretical and empirical work across species suggests that exposure to adversity may accelerate these patterns of maturation ( Callaghan and Tottenham, 2016 , Gee et al, 2013a , Herzberg et al, 2021 , Miller et al, 2020 , Silvers et al, 2016 , Thijssen et al, 2017 ). For example, stressful family environments have been linked to accelerated pubertal maturation, which in turn was associated with altered CO-amygdala rsFC, among youth in the Adolescent Brain Cognitive Development Study℠ (ABCD Study®; Thijssen et al, 2020a , Thijssen et al, 2020b ). In this way, accelerated maturation may reflect adaptation to stressful environments and promote short-term resilience to mental health problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This secondary focus of the present investigation is motivated by a common inference in the neuroimaging literature that the maturity of a developing individual’s brain size can be assessed by comparing them cross-sectionally to similar-aged peers. For example, children and adolescents with thinner cortex than similar-aged peers are often inferred as more mature, or faster-maturing, in their brain development (e.g., Paulus et al, 2019 ; Tamnes et al, 2018 ; Thijssen et al, 2020 ). In this example, the inference stems from the group-level observation that the cortex of the human brain decreases in thickness across childhood and adolescence, but fails to consider the large amount of variability neurotypically developing children can have in one given brain measure ( Wierenga et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%